2003
DOI: 10.7589/0090-3558-39.1.233
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma-associated Polyarthritis in a Reticulated Giraffe

Abstract: A case of Mycoplasma-associated polyarthritis was diagnosed in a captive reticulated giraffe (Giraffa camelopardalis reticulata). Recurrent episodes of lameness with temporary response to antimicrobial therapy characterized the disease. After the fifth episode, the giraffe was immobilized for arthrocentesis of the right front fetlock joint. Although the culture was negative, Mycoplasma sp. nucleic acid was detected in synovial fluid using polymerase chain reaction (PCR). Twelve weeks after completion of enrofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 12 publications
(18 reference statements)
0
6
0
Order By: Relevance
“…), polyarthritis (Hammond et al . ), fibropapilloma infection (Karstad & Kaminjolo ; van Dyk et al . ) and sarcoptic mange (Alasaad et al .…”
Section: Introductionmentioning
confidence: 99%
“…), polyarthritis (Hammond et al . ), fibropapilloma infection (Karstad & Kaminjolo ; van Dyk et al . ) and sarcoptic mange (Alasaad et al .…”
Section: Introductionmentioning
confidence: 99%
“…The bovine calf is known to exhibit neonatal lameness and septicemia due to insufficient colostrum intake [8]. Moreover, previous reports noted that the giraffe calf did not receive the dam’s colostrum, which might have caused the disease [4, 6]. In the present study, in calf no.…”
mentioning
confidence: 67%
“…However, the cause of the disorder was unclear. Although 2 cases of polyarthritis in the giraffe have been reported [4, 6], to the best of our knowledge, there is no report on multiple cases and the possible cause in the early stages after birth. In this study, we reviewed all clinical records and the amount of fed colostrum, and found that insufficient colostrum might be a risk factor for polyarthritis and/or phlegmon.…”
mentioning
confidence: 99%
“…4 A review of the literature revealed various reports of orthopedic problems, usually focusing on diseases of the foot. 2,5,12 Foot diseases in captive megaherbivores are easier to diagnose than problems further proximal within the limb, because clinical signs are more apparent and radiologic evaluation is straightforward. Osseous pathologies of the proximal limb are less frequently reported.…”
Section: Brief Communicationmentioning
confidence: 98%